The Prudential Regulation and Management of Foreign Exchange Risk - Abrams, Richard (IMF Working Papers; Working Paper ;, 1998)
This paper examines issues in the prudential management and regulation of foreign exchange risk. It begins with measurement issues, notably converting foreign currency items into domestic currency terms, and calculating foreign exchange positions. The focus then shifts to managing foreign exchange risks. Although the key to effective management lies in the bank's reporting and internal control systems, regulators frequently seek to limit such risks directly. This usually involves limiting the overall open position in terms of bank capital or requiring that capital be set aside against such risks.